TEKNIK PBBL: MODEL PENYEDERHANAAN DALAM PENYUSUNAN LAPORAN LABA RUGI UNTUK UMKM - Randy Kuswanto (Journal of Business And Entrepreneurship, 2025)
This study aims to develop and evaluate the effectiveness of the PBBL method (Pendapatan, Bahan Baku, Biaya Lain, and Laba/Rugi – Revenue, Raw Materials, Other Expenses, and Profit/Loss) as a simplified financial recording model designed specifically for Micro and Small Enterprises (MSEs). The study was motivated by the persistent issue of low accounting literacy among MSEs in Indonesia, which has caused most business owners to be unable to determine their monthly profits accurately. Using a developmental research approach, this study was conducted in three stages: (1) identifying problems through interviews with ten MSE owners in Jakarta, (2) designing the PBBL technique based on the principle of accounting simplicity, and (3) conducting a limited field trial involving twenty-five MSEs through an implementation and mentoring program facilitated by STIE Wiyatamandala students. Findings reveal that all interviewed MSE owners lacked proper financial records and only relied on daily cash inflows to assess performance. The implementation of the PBBL method significantly improved financial awareness and recordkeeping discipline. The main challenges identified were inconsistent recordkeeping habits and difficulties in estimating month-end inventory values. Overall, this study concludes that the PBBL method serves as an effective transitional accounting model that enhances financial literacy and profit awareness among MSEs. It can be adopted as a practical, relevant, and educational tool in community-based financial empowerment programs.